Responses of Manx Shearwaters to Handicapping and Its Implications for the Coordination of Care - Gillies, Natasha; Syposz, Martyna; Wynn, Joe; Vansteenberghe, Cécile; Guilford, Tim (Frontiers in Ecology and Evolution, 2021)
Seabirds care for their offspring in remote breeding colonies where foraging sites are distant and may be unpredictable, and where chicks are left unaccompanied for extended periods during their parents’ foraging trips, leaving them vulnerable to predation or starvation. One way to mitigate this risk is for individuals to coordinate parenting duties with their partner. Many biparental and cooperatively breeding species are now known to coordinate their care, though the mechanisms underlying this are not well understood. In Manx shearwaters (Puffinus puffinus), both parents alternate shifts of incubation in a coordinated manner. To resolve which processes may underlie this routine, we imposed a wing-loading handicap on parents to reduce their foraging efficiency, forcing them to choose between an extended foraging trip or to return to the nest before their condition has recovered to optimal levels. We found that handicapped parents took significantly longer trips than normal, to which their partner responded by lengthening their incubation shift, suggesting shift durations are not pre-determined. However, the duration of foraging trips and the mass at which foraging birds returned to the nest appeared to be mediated by the condition of the partner. These results suggest that while foraging trip duration is largely driven by the need for the foraging bird to recoup its own condition losses, information-transfer between the parents may facilitate a more cooperative mechanism whereby the decisions made by foraging birds still account for the condition of their partner.